The Effect of State Gun Laws on the Supply of Guns and Gun Crimes: A Multilevel Modeling Analysis - Continelli, T. (Health Serv Res, 2020)
Gun homicides alone cause 11 000 deaths each year. Numerous shootings in recent years, terrorist and otherwise, have sparked heated debates about gun control policy, particularly with regard to Second Amendment issues. Such discussions are more often than not driven by political and philosophical ideology, rather than empirical data. The self‐imposed ban on the dissemination of gun‐related statistics on the part of the Centers for Disease Control has created difficulty in obtaining data, particularly at the sub‐state level. Furthermore, the majority of previous research has not examined the effect on crimes that are gun specific, that is, homicides or robberies committed using guns versus all homicides or robberies. The objective of this research is to examine the multiple relationships between gun ownership and gun crimes at the sub‐state level and to then examine the effect of state‐level gun laws on the sub‐state relationships via multilevel modeling. This research involves two separate units of analysis, counties and states. Initial multivariate regression was conducted on a subset of counties in the United States examining the relationship between the percentage of all households with at least one gun, and both the gun homicide rate as well as the gun robbery rate. Data on gun ownership were obtained from the CDC's BRFSS SMART County‐level data files from the mid‐2000s. These data are sampled and weighted to be representative of the entire county. A total of 218 weighted, aggregated counties were used from two separate non‐overlapping years combined. Gun crime data were obtained from the FBI Uniform Crime Reports, which provides total universe data on crimes, including the number committed with a gun. State gun law rankings were obtained from the Law Center to Prevent Gun Violence, which quantifies state gun laws into a numeric index. Standard county‐level control variables such as race, income, poverty, region of the country, level of education, and population density were employed. Multilevel models were then run overlaying state gun laws with county‐level data. The population studied included adults age 18 and older who responded to the Centers for Disease Control's BRFSS survey questions, as well as all gun crimes known to the police. In traditional multivariate analysis, a higher percentage of households with guns was associated with lower gun robbery rates as well as lower gun homicide rates. Multilevel modeling using state gun laws indicated that more restrictive gun laws were also associated with lower gun robbery and homicide rates. The percentage of households with guns remained negative and significant in the multilevel models. Moreover, restrictive state gun laws were associated with lower gun ownership rates at the county level. Both legal gun ownership and more restrictive state gun laws are associated with lower rates of violent gun crimes (robbery and homicide). The results unexpectedly provide support for both pro‐ and anti‐gun positions. This suggests that causal patterns are more complex than either position might indicate, and public health policies on gun supply and restriction would be better informed by empirical analysis.